Compressive Strength and Flexural Behaviour of Foamed Concrete Slab Containing Hybrid Fibres - Mohamad, Noridah; Lakhiar, Muhammad Tahir; Anis Aqilah; Ashfaque Ahmed Jhatial; Steafenie George (Recent Trends in Civil Engineering and Built Environment, 2020)
Foam concrete has been used widely in the construction industry, due to its lightweight and easy handling. The foam concrete (FC) mixture in this study can contribute to the sustainability of construction due to the utilization of hybrid fibers, which are coir fiber (CF) and steel fiber (SF). The aim of this study is to investigate the compressive strength, flexural strength and crack pattern of precast foamed concrete slab incorporating with hybrid fibers. The three different mixtures of foam concrete were used to cast three different types of specimens, namely control slab (0% fiber), slab with 3% steel fiber, and slab with 3% steel fiber and 1% coir fiber.  Compressive strength test was conducted on the cube specimens while four-point bending test was conducted on the slab specimens. It was found that the compressive strength and ultimate load of FC containing SF and CF were 50% and 134% increased, respectively, compared to the control sample. Meanwhile, cracking pattern shows  less cracks  appeared on surface of FC slab with 3% SF and 1% CF  compared to the control slab. Subsequently the load-deflection profile described that FC-3% SF-1% CF is more ductile compared to the control slab.